The impacts of tourism development on community well-being in Langkawi: the case of Kampung Padang Puteh, Mukim Kedawang - Ibrahim, Mohamad Syahrul Nizam; Abdul Halim, Sharina; Ishak, Mohd Yusoff (Institution for Marine and Island Cultures, 2019)
Tourism has assisted the development of environmental, economic, social and cultural aspects of island communities. While there are some previous studies on the impacts of tourism development across Langkawi, it is necessary to consider the impacts of tourism development on individual island communities. Kampung Padang Puteh, Mukim Kedawang, Langkawi is located on the route between the island's main tourism attraction areas, Pantai Cenang and Pantai Tengah (which are highly affected by tourism activities). This purpose of this study is to examine the impacts of tourism development with regard to benefits and challenges based on the local community perspective. A combination of quantitative and qualitative approaches was used in this study through a questionnaire to 49 household representatives, and individual interviews that were conducted with 16 selected key informants in Kampung Padang Puteh. Analysis of mean, Spearman's rho correlation and qualitative approaches were used to interpret the data. The main findings concern community well-being and the benefits and challenges of tourism development impacts for the local community. It was found that the local community have improved their socioeconomic level through employment opportunities, additional income and language skills. While social ties were still good, negative aspects pose challenges.